Morphological and visual cues in compound word reading: Eye-tracking evidence from Hebrew. Issue 12 (December 2020) - Kuperman, Victor; Deutsch, Avital
Hebrew noun–noun compounds offer a valuable opportunity to study the long-standing question of how morphologically complex words are processed during reading. Specifically, in some morpho-syntactic environments, the first (head) noun of a compound carries a suffix—a clear orthographic marker of being part of a compound—whereas in others it is homographic with a stand-alone noun. In addition to this morphological cue, Hebrew occasionally employs hyphenation as a visual signal that two nouns, which are typically separated by a space, are combined in a compound. In a factorial design, we orthogonally manipulated the morphological and the visual cues and recorded eye movements of 75 proficient Hebrew readers while they read sentences with embedded compounds. The effect of hyphenation on reading times was inhibitory. This slow-down was significantly weaker in compounds where the syntactic relation between constituents was overtly marked by a suffix compared with compounds without a morphological marker. We interpret these findings as evidence that hyphenation is largely a redundant cue but morphological markers of compounding are psychologically valid cues for semantic integration of compounds. We discuss the implications of this finding for accounts of morphological processing.